EFEKTIVITAS PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA GAMPONG (APBG) DALAM KONSEP REINVENTING GOVERNMENT - Najah, Nailun; Alisman (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This study aims to determine the effectiveness of APBG management in the concept of reinventing government. The research design used is descriptive qualitative research with observation data collection methods. Researchers conducted direct observations at the village office in Pasi Pinang Village, conducted interviews with the village treasurer regarding APBG funds and conducted documentation. The research location is in Pasi Pinang Village, Meureubo District, West Aceh Regency. The results of the study show that the Pasi Pinang Village Government has started to implement the concept of Reinventing Government as evidenced by the existence of village-owned businesses and village assets managed by BUMG as one of the Village's Original Income (PAG). The PAG in 2019 that the village received was very effective (100%) with an income of IDR 56,375,000, exceeding the target stated in the APBG of IDR 36,000,000. In 2020 PAG was less effective (69%) because it decreased by Rp. 24,700,000 so it did not reach the target set by the APBG of Rp. 36,000,000. The stipulation of a Governor's Regulation (Pergub) regarding the prohibition of gampong business results in the form of the distribution of Galian C and also the farm shop business is the cause of the decline in income and the village is experiencing bankruptcy from the gampong business in the form of buying and selling activities on the farming business. People often complain about income that does not match their capital so that the results from these efforts are not given to BUMG. Therefore, in 2020 the business will no longer be a village business